Analisis Badan Usaha Milik Desa (BUMDes) Dalam Struktur Anggaran Pendapatan Dan Belanja Desa (APBDes) Di Kecamatan Meurah Dua Kabupaten Pidie Jaya - Laura Nonita; Agus Nugroho; Zukarnain Zulkarnain (Fakultas Pertanian, Universitas Syiah Kuala, 2021)
In this study, the problem to be seen is how the pattern of APBDes utilization against BUMDes in 19 villages located in Meurah Dua Sub-district and how much BUMDes funds are distributed to APBDes in Meurah Dua Sub-district. This study aims to see the pattern of APBDes utilization against BUMdes and to see BUMDes funds that are distributed in the APBDes. The results of this study indicate that the pattern of using APBDes funds for BUMDes in Meurah Dua Sub-district is generally the funds distributed in BUMDes activities by looking at the conditions and potential in each village and the funds or profits from this BUMDes activity still have no value or have not contributed to the income typical of his village.